Viva Zapata! Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Assassination scene of Emiliano Zapata (Marlon Brando.) Zapata falls to the ground as lines of gunmen on two roof levels firing down at him. RESTRICTED USE